Investigation of pH2S influence on 3% Cr tubing steel corrosion behaviours in CO2–H2S–Cl− environment. (October 2015) - Yan, W.; Deng, J.; Zhu, P.; Xing, X.
Abstract : A series of experiments were conducted in autoclave to investigate corrosion properties of low Cr oil country tubular goods in CO2 /H2 S saturated brine solution (3 wt-%NaCl) at 90°C. Test material is 3Cr-80, which is gradually accepted in oil and gas industry, especially for downhole tubing and casing. The CO2 partial pressure was fixed at 4·0 bar in all experiments, and the H2 S partial pressure was varied from 0, 2, 4, 8, 20, 40 and 800 mbar to 4000 mbar (4 bar). The results show that when the pH2 S varied at a lower range (2–40 mbar), 3Cr-80 materials' corrosion rates were restricted, and coupons' surface morphologies became glossy compared to the pure CO2 corrosion. Under the condition of pH2 S = 800 mbar, H2 S no longer have a retardation effect on CO2 corrosion but acceleration. The average corrosion rate was higher than pure CO2 corrosion. When the pH2 S rise to 4000 mbar (equal to the CO2 partial pressure), 3Cr corroded much more severe and serious mesa attack was observed.